Analysis of radon concentration and gamma dose rate in residential houses of Ambon and Seram Islands, Maluku - WAHYUDI WAHYUDI; ILMA DWI WINARNI; MUJI WIYONO; KUSDIANA KUSDIANA (Jurnal Natural, 2021)
Radon concentration analysis in the residential houses on Ambon and Seram Island - Maluku through the passive method using the CR-39 nuclear track detector has been studied. The CR-39 nuclear track detector was installed inside the residential houses for 3 months. After finishing the exposure, the detector was taken and etched using 6.25 N NaOH solution. The nuclear track of radon in the CR-39 was read by a microscope with 400 times magnification. From the results of reading the track, determination of radon concentration in the houses was calculated. The results of the analysis showed that radon concentrations in the residential houses of Ambon and Seram Islands, Maluku at the low level were in the range of 2.56 ± 0.18 Bq/m3 to 59.65 ± 4.22Bq/m3 with an average value of 28.42 ± 1.98 Bq/m3. The average concentration of radon is still below the average radon concentration in the world of 50 Bq/m3. The value of dose received by the population due to exposure of radon and gamma radiation in the range of 0.90-1.44 mSv/year. There is a positive correlation between radon concentration value and total radiation doses received by the population for a year. This data can be used in the study of radiation safety for the Ministry of Health and as a contribution to Indonesia in the international community about monitoring environmental radiation from radon concentrations in residential houses